Ethical And Professional Frameworks For Addressing Violence Against Health Care Workers: A Health Security Perspective (The Review of Diabetic Studies, 2024)
Background: Violence against health care workers has become a pervasive and escalating global concern, encompassing behaviors ranging from verbal aggression to physical assault. Such violence disrupts clinical care, inflicts psychological harm, contributes to burnout, and threatens the stability of health systems. The article highlights how nurses and frontline clinicians experience disproportionate exposure to these risks due to their roles and continuous patient contact. Aim: This paper aims to examine the ethical tensions, professional responsibilities, and organizational frameworks necessary for managing violence toward health care workers, emphasizing ethical reasoning, clinical culture, and institutional accountability.Methods: A structured ethical analysis was conducted drawing on professional guidelines, clinical experience, and institutional practices. The paper synthesizes ethical principles—beneficence, nonmaleficence, autonomy, justice—alongside operational strategies such as de‑escalation, team‑based responses, trauma‑informed care, and leadership accountability. It reviews contextual factors influencing clinician responses, including urgency of care, patient decision‑making capacity, threat severity, and institutional culture.Results: The analysis shows that ethical management requires balancing patient rights with staff safety, applying proportional responses based on clinical urgency and threat level, and ensuring equity in institutional responses. Trauma‑informed approaches reduce escalation, while structured de‑escalation training and behavioral response teams enhance safety and consistency. Leadership engagement emerges as critical for policy enforcement, cultural change, and staff support. Conclusion: Violence in health care settings is a multifactorial challenge demanding coordinated ethical, clinical, and organizational action. Integrating trauma‑informed practice, de‑escalation skill‑building, and leadership accountability strengthens safety, preserves dignity, and promotes equitable and sustainable clinical environments.